Winnipeg's Pediatric Cardiac Inquest - A Nursing Perspective - Youngson, Carol (Operating Room Nurses Association of Canada Journal, 1999)
What happened to my colleagues and me over the past 5 years is something that every nurse has experienced in some way and to some degree in his or her career. What happened to us can happen to any nurse - anywhere. Our story will ring true to all nurses who have been in the front lines of the health care system, because that is what nurses are ...the front line caregiver. One of my colleagues put it so well... “ we are the ones who hear, see and do for those who cannot”.